For the development of financial instruments for environmental protection. (Journal of Economic Research & Business Administration, 2016)
The problem of landfills is becoming today one of the most important in the world. Her decision urgently requires mobilization of science, business and the public each country’s rapid problem solving rational use of the planet’s resources and the protection of its environment.The rate of growth of landfills in developed countries are ahead of all predictions did before : the world population is increasing annually by 1.5-2%, and the volume of landfills of the world – at 6 % per year, ie increased by 3-4 times faster. . .The problem of effective, environmentally – oriented approach in the management of natural resources is largely due to the economic aspect. This is especially true in a market economy, which provides some leeway In this context, we can talk about the formation of effective economic mechanism of nature.It is also necessary to take into account the fact that the relationship between the environment and economic growth is rather complicated .
Keywords: «green» economy; commodity waste; landfill; environment; waste management.